Single-Molecule Electronics An Introduction to Synthesis, Measurement and Theory - Kiguchi, Manabu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents a multidisciplinary approach to single-molecule electronics. It includes a complete overview of the field, from the synthesis and design of molecular candidates to the prevalent experimental techniques, complemented by a detailed theoretical description. This all-inclusive strategy provides the reader with the much-needed perspective to fully understand the far-reaching ramifications of single-molecule electronics. In addition, a number of state-of-the-art topics are discussed, including single-molecule spectro-electrical methods, electrochemical DNA sequencing technology, and single-molecule chemical reactions. As a result of this integrative effort, this publication may be used as an introductory textbook to both graduate and advanced undergraduate students, as well as researchers with interests in single-molecule electronics, organic electronics, surface science, and nanoscience. .
Molecular Electronics: A brief overview of the status of the field -- Methods to determine electrical conductance of single-molecule junctions -- Characterization of the single molecular junction -- Molecular wires: An overview of the building blocks of molecular electronics -- Insulated Oligothiophenes -- Synthesis and Physical Properties of Three-dimensionally Insulated Molecular Wires -- Orbital rule for electron transport of molecular junctions -- Theoretical aspects of quantum transport and computational modeling of molecular electronic device -- Single-Molecule Sequencing. .
Keywords: Physical chemistry; Nanoscience; Nanotechnology; Nanochemistry; Electronics; Physical Chemistry; Nanophysics; Nanotechnology; Nanochemistry; Electronics and Microelectronics, Instrumentation